2021
DOI: 10.3390/s21103525
|View full text |Cite
|
Sign up to set email alerts
|

Cuffless Blood Pressure Measurement Using a Smartphone-Case Based ECG Monitor with Photoplethysmography in Hypertensive Patients

Abstract: The availability of simple, accurate, and affordable cuffless blood pressure (BP) devices has the potential to greatly increase the compliance with measurement recommendations and the utilization of BP measurements for BP telemonitoring. The aim of this study is to evaluate the correlation between findings from routine BP measurements using a conventional sphygmomanometer with the results from a portable ECG monitor combined with photoplethysmography (PPG) for pulse wave registration in patients with arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…The performance of the two and three-channel approaches are similar, while the performance improves again by around 25% when all four signals are used in combination. The same pattern was seen for both SBP and DBP even though SBP performed worse than DBP in all cases, which is a typical observation from the literature as well [12][13][14][15][16]18,[20][21][22][23][24][25][26][27]64].…”
Section: Experiments 1: Train and Test On Uci Datasetsupporting
confidence: 79%
“…The performance of the two and three-channel approaches are similar, while the performance improves again by around 25% when all four signals are used in combination. The same pattern was seen for both SBP and DBP even though SBP performed worse than DBP in all cases, which is a typical observation from the literature as well [12][13][14][15][16]18,[20][21][22][23][24][25][26][27]64].…”
Section: Experiments 1: Train and Test On Uci Datasetsupporting
confidence: 79%
“…Using single biomedical signals such as ECG or PPG to estimate the BP including systolic blood pressure (SBP) and diastolic blood pressure (DBP) can increase the value of smart devices [3,23]. Therefore, the effects of ECG and PPG signals are examined and then three types of inputs were designed as I(ECG), I(PPG), and I(ECG, PPG).…”
Section: Results Of Feature Evaluation and Selectionmentioning
confidence: 99%
“…Cuff-based BP monitoring devices are commonly used to estimate BP, but these devices are inconvenient and uncomfortable for patients. To overcome some of these problems, many researchers developed cuffless BP estimations, which are based on pulse transit time (PTT), photoplethysmography (PPG), or electrocardiogram (ECG) [2][3][4][5]. Generally, PTT refers to the time it takes a pulse wave to travel between two arterial sites and can be calculated by using ECG and PPG [2].…”
Section: Introductionmentioning
confidence: 99%
“…Such methods are essential for the clinical application of sensor arrays. Existing studies have shown that pulse wave abnormalities are closely associated with cardiovascular disorders, which provides strong evidence for the assessment of the physiological and pathological status of individuals [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%